Corporate Social Responsibility's (CSR) Impact on Financial Performance: Moderating Effects of Earnings Management and Leverage - Rita Kusumawati; Nurul Hilmi Asyilah; Iskandar Bukhori (Universitas Muhammadiyah Yogyakarta, 2022)
Research aims: This research attempts to test the impact of CSR on financial performance, with earnings management and leverage acting as moderating factors.Design/Methodology/Approach: The manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2019 served as the study object. Purposive sampling was utilized in sample selection, yielding 228 samples. Multiple linear regression and moderated regression analysis were the analytical techniques used in this study, with the EViews 10 program being used for the fixed effect model.Research finding: The analysis results indicated that CSR had no significant effect on financial performance; earnings management could not moderate the influence of CSR on financial performance; leverage could moderate the effect of CSR on financial performanceTheoretical contribution/Originality: The study's findings offer insight and input for company management in terms of implementing CSR and its relation to company performance.Practitioner/Policy implication: The findings of this study should be helpful to stakeholders in selecting how to implement a CSR program in their company.Research limitation/Implication: This study only uses ROE as an indicator of financial performance, the research period is only 5 years, and CSR data is only based on what is stated in the company's financial statements.